Efficacy of panitumumab in older patients with metastatic colorectal cancer: a retrospective analysis using the database of the Hellenic Oncology Research Group (HORG). Issue 1 (January 2019) - Asimakopoulou, Natalia; Souglakos, John; Kentepozidis, Nikolaos; Karampeazis, Athanasios; Kotsakis, Athanasios; Ziras, Nikolaos; Makrantonakis, Paris; Prinarakis, Efthimios; Vamvakas, Lambros; Georgoulias, Vassilis; ,
Abstract: Background: Although colorectal cancer (CRC) is a disease of the older patients, older patients are under-represented from randomized trials. Herein we conducted a retrospective analysis for the effect of panitumumab in the management of older patients (≥65 years) patients with metastatic CRC (mCRC) in the Hellenic Oncology Research Group's (HORG) database. Methods: Τhe efficacy of panitumumab-based chemotherapy as front-line treatment in older patients with mCRC was assessed. Results: In total, 110 older patients with KRAS exon 2 wild type tumors were treated with chemotherapy plus panitumumab. The median age was 74 years; 69.9% of the patients were male, with left-sided primary tumors (78.2%), ECOG Performance Status 0–1 (95.4%) and median number of metastatic sites 2. Sixty-two (Overall Response Rate-ORR: 56.4%; 95% CI: 48.8%–68.1%) achieved an objective response, while 21 (19.1%) had stable disease. Median Progression free survival (PFS) was 9.4 months (95% CI: 7.8–11.0 months) and median Overall survival (OS) 23.0 months (95% CI: 20.6–25.3 months). Additionally, a statistically significant difference in ORR (62.7% vs. 33.3%; p  = .014), median PFS (12.9 vs. 5.7 months; p  = .001) and median OS (31.6 vs. 16.7 months; p  < .001) was observed in patients with left-sided compared to right-sided primary tumor. There was no treatment-related death. Grade 3–4 toxicities were neutropenia (8.9%) and diarrhea (14.5%) whereas skin rash grade 2 or 3 was recorded in 41.1% and 10.7%, respectively. Conclusions: The results of this retrospective study provide the evidence that combination chemotherapy plus panitumumab is active and well tolerated in older patients with mCRC.